2014
DOI: 10.1089/tmj.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Experience of Remote Medical Education in Asia

Abstract: Background: Moving images are often essential in medical education, to learn new procedures and advanced skills, but, in the past, high-quality movie transmission was technically much more challenging than transmitting still pictures because of technological limitations and cost. Materials and Methods: We established a new system, taking advantage of two advanced technologies, the digital video transport system (DVTS) and the research and education network (REN), which enabled satisfactory telemedicine on a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…A more interesting finding was reported by Holmner et al who showed that by replacing a physical meeting with telemedicine, carbon reduction can be achieved, thus offering a greener choice than conventional meeting 5. As shown in the decade-long result, endoscopy-related teleconferences are gaining popularity 2. Recent advances in the field of diagnostic and therapeutic endoscopy “prompted” a wave of mutual learning from each other 2 6 7 8.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A more interesting finding was reported by Holmner et al who showed that by replacing a physical meeting with telemedicine, carbon reduction can be achieved, thus offering a greener choice than conventional meeting 5. As shown in the decade-long result, endoscopy-related teleconferences are gaining popularity 2. Recent advances in the field of diagnostic and therapeutic endoscopy “prompted” a wave of mutual learning from each other 2 6 7 8.…”
Section: Discussionmentioning
confidence: 96%
“…As shown in the decade-long result, endoscopy-related teleconferences are gaining popularity 2. Recent advances in the field of diagnostic and therapeutic endoscopy “prompted” a wave of mutual learning from each other 2 6 7 8. Chung et al accurately pointed out that the conventional ways of disseminating knowledge via publication in journals and books cannot match the pace of rapid development in the field of therapeutic endoscopy and laparoscopic surgery 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We seek to build trauma management capacity in a manner that is globally scalable in the native languages of under-resourced nations, many of which now have Internet access. 27 Thus, our MOOC design provides a no-cost, high-quality education, targeted for an expansive audience of laypersons. We then supplement MOOC learning with the live two-day workshop and interactive assessments to deliver a “dual-layer” MOOC, 28 which may serve as the ideal model to confer both clinical knowledge and interactional skills in a multinational force of first responders.…”
Section: Mooc For Global Scalabilitymentioning
confidence: 99%
“…Shimuzu et al, [90] in a paper entitled "Ten-year experience of remote medical education in Asia" Table 2). The two main areas were endoscopy and surgery, with 113 (31%) and 106 (29%) events, respectively followed by health care and nursing.…”
Section: The Use Of Internet In Asian Cme/cpd Deliverymentioning
confidence: 99%